Corporate Risk around the World - Nenova, Tatiana (The World Bank, 2000)
January 2000 - Corporate financing patterns around the world reflect countries' institutional environments. Weaknesses in the corporate sector have increasingly been cited as important factors in financial crises in both emerging markets and industrial countries. Analysts have pointed to weak corporate performance and risky financing patterns as major causes of the East Asian financial crisis. And some have argued that company balance sheet problems may also have played a role, independent of macroeconomic or other weaknesses, including poor corporate sector performance. But little is known about the empirical importance of firm financing choices in predicting and explaining financial instability. Firm financing patterns have long been studied by the corporate finance literature. Financing patterns have traditionally been analyzed in the Modigliani-Miller framework, expanded to incorporate taxes and bankruptcy costs. More recently, asymmetric information issues have drawn attention to agency costs and their impact on firm financing choices. There is also an important literature relating financing patterns to firm performance and governance. Several recent studies have focused on identifying systematic cross-country differences in firm financing patterns - and the effects of these differences on financial sector development and economic growth. They have also examined the causes of different financing patterns, particularly countries' legal and institutional environments. The literature has devoted little attention to corporate sector risk characteristics, however, aside from leverage and debt maturity considerations. Even these measures have been the subject of few empirical investigations, mainly because of a paucity of data on corporate sectors around the world.